Test of Type of Decomposer on Compost Making from Waste of Oil Palm Fronds on The Quality of Compost Yield - Reni Rhys; Lukman Adlin Harahap; Ainun Rohanah (Universitas Sumatera Utara, 2016)
Compost is a result of plant waste decomposition that caused by microorganism decomposition. Therefore it needs a decomposer to fasten organic decomposition. This research was done in April until August 2015 in Soil Laboratory, Agricultural Technology Research Agency of North Sumatera and Agricultural Engineering Laboratory, Faculty of Agriculture, USU, Medan, using non factorial completely randomized design with four types of MOL, i, e, orange MOL, mango MOL, pinneapple MOL, and papaya MOL. Measured parametres were comparison of C/N, pH and yield. The results showed that there was no different effect given by orange MOL, mango MOL, pinneapple MOL, and papaya MOL in the case of C/N, pH and yield. Key words: Compost, decomposer, palm frond.